Growth performance of gouramy (Osphronemus gouramy) with the addition of activated charcoal from tuna (Thunnus sp) bone waste in feed - Nazlia, Suraiya; Nurhayati, Nurhayati; Riski, Ade Maya; Aprita, Ika Rezvani; Sabri, Mustafa; Afriana, Safrida; Febri, Suri Purnama (Acta Aquatica: Aquatic Sciences Journal, 2023)
This study aims to determine the effect of adding activated charcoal from tuna bones on the growth of gouramy. This research was conducted at the Integrated Laboratory of the Faculty of Fisheries, Abulyatama University, Aceh. The test fish used were gouramy seeds with a size of 2-3 g and 5-6 cm. This study used a non-factorial completely randomized design, consisting of four treatments and three replications, including A (control; without the addition of activated charcoal), B (addition of 1% activated charcoal in feed), C (addition of 2% activated charcoal in feed), and D (addition of 3% activated charcoal in feed) for 60 days of the rearing period. Fish are kept in an aquarium with a size of 60 x 40 x 40 cm as many as 10 fish per container with a water level of 30 cm. During the maintenance period, fish were fed twice a day at satiation. Parameters measured included survival, absolute weight and length growth, daily growth rate (LPH), and feed conversion ratio (FCR). The data were analyzed using analysis of variance (ANOVA). if significantly different, continue further testing using Duncan. The results showed that the addition of 2% tuna bone activated charcoal in feed affected growth performance including in absolute weight and length growth, SGR, and gave the best value on FCR and SR of 8.98 ± 0.20 g; 3.36±0.13cm; 2.60±0.11; 1.63; 100±0.00%.Keywords: activated charcoal; Osphronemus gouramy; growth; fish bone